The Application of Think-Talk-Write (TTW) In Teaching Writing Narrative Text at SMAN 1 Polewali - Humaerah, Nurul Husnul (La Parole : Journal of Language Teaching and Pedagogy, 2018)
The researcher conveyed that this aims to test students' understanding of writing narrative text. The author uses a quasi-experimental method and applies a non-equivalent control group design. The method used is cluster random sampling. The instrument used in this study was a narrative text consisting of two kinds of tests, namely pre-test and post-test. The results showed that the posttest results of the experimental group students were higher than those of the control group students. This is evidenced by the posttest mean score of the experimental group (77.85) which is higher than the control group (51.65). This is also evidenced by the t-test value (3.58) which is greater than the t-table value (2.042). Thus it can be concluded that the application of TTW can improve students' narrative writing skills. Penelitian ini bertujuan untuk menguji pemahaman siswa tentang menulis narrative teks. Penulis menggunakan metode eksperimen semu dan menerapkan desain kelompok kontrol non ekuivalen. Metode yang digunakan adalah cluster random sampling. Instrumen yang digunakan dalam penelitian ini adalah teks naratif yang terdiri dari dua macam tes yaitu pre-test dan post-test. Hasil penelitian menunjukkan bahwa hasil posttest siswa kelompok eksperimen lebih tinggi daripada posttest siswa kelompok kontrol. Hal ini dibuktikan dengan nilai rata-rata posttest kelompok eksperimen (77,85) lebih tinggi dibandingkan kelompok kontrol (51,65). Hal tersebut juga dibuktikan dengan nilai t-test (3,58) yang lebih besar dari nilai t-tabel (2,042). Dengan demikian dapat disimpulkan bahwa penerapan TTW dapat meningkatkan kemampuan menulis naratif siswa.